Quality Learning Innovation Through Inspiring Active Learning at MA Al Ijtihad Danger Masbagik - Surya Bayu Ansori (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Indonesian national education is facing two major challenges: internal challenges such as low rankings in international education studies and high levels of corruption, and external challenges such as global dynamics such as the implementation of the ASEAN and APEC free markets. These conditions demand reforms in learning practices to improve the quality of education. This study aims to examine the application of inspiring active learning as an innovation effort in the teaching and learning process. The method used is qualitative action research with an interactive analysis approach from the Miles and Huberman model. The study was conducted at MA AL Ijtihad Danger Masbagik for one month, from December to January 2023, with research subjects including the principal, deputy principal of curriculum, and subject teachers. Data collection techniques used observation, interviews, and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate that improving the quality of learning can be achieved through inspiring active learning strategies, which include: creating learning activities that motivate active participation, building an inspiring learning climate, and fostering high levels of cooperation in the classroom.